2019
DOI: 10.1186/s12879-019-4341-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal adherence to maternal antiretroviral therapy and infant Nevirapine prophylaxis from 6 weeks to 18 months postpartum amongst a cohort of mothers and infants in South Africa

Abstract: Background Despite improved policies to prevent mother-to-child HIV transmission (MTCT), adherence to maternal antiretroviral therapy (ART) and infant Nevirapine prophylaxis (NVP) is low in South Africa. We describe ART adherence amongst a cohort of HIV-positive mothers and HIV-exposed but uninfected infants from 6 weeks until 18 months post-delivery and identify risk factors for nonadherence. Methods Data were collected in 2012–2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Accordingly, women who disclosed their HIV/AIDS status were 4.38 (95%CI: 1.79, 10.70) times more likely to have good adherence to ART than those who had didn’t disclose their HIV/AIDS status to their partner. A study on longitudinal adherence to maternal ART in South Africa similarly revealed that non-disclosure of HIV serostatus was negatively associated with good adherence [ 38 ]. According to a study conducted in KwaZulu-Natal, and Eastern Cape, South Africa, the issue related to disclosure was a reason for sub-optimal adherence to ART medications among women [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, women who disclosed their HIV/AIDS status were 4.38 (95%CI: 1.79, 10.70) times more likely to have good adherence to ART than those who had didn’t disclose their HIV/AIDS status to their partner. A study on longitudinal adherence to maternal ART in South Africa similarly revealed that non-disclosure of HIV serostatus was negatively associated with good adherence [ 38 ]. According to a study conducted in KwaZulu-Natal, and Eastern Cape, South Africa, the issue related to disclosure was a reason for sub-optimal adherence to ART medications among women [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We relied on the mother or caregiver’s report in measuring adherence of the infant to nevirapine prophylaxis. Studies done in South Africa [ 9 , 13 , 19 ], have reported levels of non-adherence to infant nevirapine prophylaxis ranging from 12.3%–30% within which range the incidence of non-adherence in our study falls. The reported non-adherence rates vary across study contexts because different methods were used while measuring infant adherence.…”
Section: Discussionmentioning
confidence: 53%
“…The majority of the women in our cohort who never received nevirapine for the baby actually had a non-clinic delivery, mostly a home delivery. Studies done in Zambia [ 13 ], South Africa [ 19 ] and a systematic review for sub-Saharan Africa [ 12 ] have demonstrated the association between home delivery and non-adherence to infant prophylaxis. Home deliveries have also been associated with the mother not receiving the nevirapine syrup for the baby from the health worker at the time of delivery [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To reach the ambitious targets of EMTCT, ART adherence and programme retention are critical; unfortunately, both present unique challenges over the course of pregnancy and breastfeeding [65‐68]. In their review of the literature, Stover, et al estimated that maternal PMTCT retention to ART programmes at 80% at time of delivery [47].…”
Section: Resultsmentioning
confidence: 99%